Growth patterns and condition factors of fish in the Celike River, leuser ecosystem area, East Aceh, Indonesia - Waliul Perdana Adli; Maghfiriadi Furqan; Maulizar Siti; Julismi Al; Dawami Muhammad; Nur Firman M. (BIO Web of Conferences)
Fish growth patterns are the process of increasing the size and weight of a fish's body that occurs during its lifetime. This growth pattern is influenced by genetic factors, the environment, food availability and the physiological condition of the fish. Research on Growth Patterns and Condition Factors of Fish in the Celike River in the Leuser Ecosystem Area of East Aceh aims to determine the size of fish and provide an overview of fish growth patterns by analyzing the relationship between length and weight and fish condition factors. The method used is a purposive sampling method, namely determining the location of research station based on consideration of habitat characteristics in locations that are thought to have a high presence of fish, are easy to reach and represent the Celike River area in the Leuser Ecosystem Area. This research was carried out in July 2024. The total number of fish obtained was 122 individuals from 10 species belonging to seven families, namely Cyprinidae, Sisoridae, Clariidae, Channidae, Cichlidae, Balitoridae, Aplocheilus. There are two dominant species caught at this location, namely Tor soro and Tor tambra. Tor tambra obtained during the study amounted to 40 individuals with a total length of 70.09 - 434.4 mm and a weight of 3.96 - 811.05 g. Tor soro) obtained during the study amounted to 34 individuals with a total length of 61.79 - 144.33 mm and a weight of 2.89 - 32.5 g. The growth pattern of fish in the Celike River with eight fish species is negative allometric, two fish species are isometric and positive allometric, with condition factor values ranging from 0.07 to 8.88.